2017
DOI: 10.1126/sciadv.1602536
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical deformation induces depolarization of neutrophils

Abstract: In vivo–mimicking mechanical deformations quickly depolarize neutrophils—a mechanism potentially failing in acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 60 publications
5
99
0
Order By: Relevance
“…The physiological benefits of having the lungs as a site of depriming have already been postulated (56,77) and the consequences for pathology hypothesized (16,103). In fact, contemporaneous with our unpublished data showing that mechanical deformation can deprime soluble agonist-activated neutrophils (14) there is emerging clinical evidence that the healthy human lungs selectively retains primed neutrophils in order to deprime them and rerelease them into the systemic circulation as resting cells (104). This recent work suggested that the yet-to-be-identified physiological depriming mechanism(s) may fail in patients with ARDS, resulting in increased numbers of primed neutrophils within the systemic circulation (104).…”
Section: Priming and Depriming By Other Mechanical Stimuli (Constrictsupporting
confidence: 71%
See 4 more Smart Citations
“…The physiological benefits of having the lungs as a site of depriming have already been postulated (56,77) and the consequences for pathology hypothesized (16,103). In fact, contemporaneous with our unpublished data showing that mechanical deformation can deprime soluble agonist-activated neutrophils (14) there is emerging clinical evidence that the healthy human lungs selectively retains primed neutrophils in order to deprime them and rerelease them into the systemic circulation as resting cells (104). This recent work suggested that the yet-to-be-identified physiological depriming mechanism(s) may fail in patients with ARDS, resulting in increased numbers of primed neutrophils within the systemic circulation (104).…”
Section: Priming and Depriming By Other Mechanical Stimuli (Constrictsupporting
confidence: 71%
“…Moreover, mechanical stimuli can prime and activate neutrophils. Deformation in narrow channels led to activation and pseudopod formation (14,53), contactless stretching by optical forces yielded similar results (14).…”
Section: Neutrophil States: Resting Versus Activatedmentioning
confidence: 58%
See 3 more Smart Citations